Explaining academic frustration based on personality traits and coping strategies - . .; . . (پژوهش در نظام‌های آموزشی, 2016)
Feeling of frustration is a common experience that has had its harmful effects on the learning and academic performance of students in the focus of attention of researchers. In this research, the role of Ali's characteristics of personality traits and coping strategies in explaining academic frustration was investigated. Participants included 718 students (380 girls and 338 boys) from Shiraz high schools selected by a cluster sampling method. To collect data, a short version of the Goldberg personality trait questionnaire, the scale of coping strategies with academic bells, and the degree of boredom associated with the class and learning was used. In order to investigate the model using structural equation method and to determine the role of mediation of coping strategies, the Bootstrap method and Baron and Kenny stages were used in AMOS software. The results of the study showed that, except for consensus, other personality factors predict academic frustration. Avoidance cognitive coping strategies will mediate the effect of task-oriented traits and the openness of experience on academic frustration. Avoiding behavioral strategy also mediates the impact of extraversion, duty and openness on academic frustration. In addition, the study of fit indices indicated that the model was consistent with the observations. The implications of the findings in the light of theoretical foundations and previous research are the subject of this article.